Metaphysical Explanations for Modal Normativists. (14th September 2020) - Locke, Theodore
I expand modal normativism, a theory of metaphysical modality, to give a normativist account of metaphysical explanation . According to modal normativism, basic modal claims do not have a descriptive function, but instead have the normative function of enabling language users to express semantic rules that govern the use of ordinary non-modal vocabulary. However, a worry for modal normativism is that it doesn't keep up with all of the important and interesting metaphysics we can do by giving and evaluating metaphysical explanations. So, I advance modal normativism by arguing that metaphysical explanations also have a normative rather than descriptive function. In particular, non-causal explanatory claims have formal and semantic properties that make them expressively stricter than basic modal claims and so are better suited to express fine-grained aspects of semantic rules. A major payoff of my normativist account of metaphysical explanations is that it yields a plausible story about how we come to evaluate and know metaphysical explanations—we do this primarily by conceptual analysis. I also respond to a number of objections, including the objection that the epistemic payoffs of my view are not worth the metaphysical costs.